Designing Home Security With Esp32-Cam and IoT-Based Alarm Notification Using Telegram - Hery Kurniawan; Susanto Hariyanto (bit-Tech, 2023)
Nowadays, technological advances have entered human life. One of the security system solutions is the use of Closed Circuit Television (CCTV) as a monitoring medium, but it is still lacking. This is because more and more crimes are committed in homes where the owner is away. As a result, each home needs a security system that can protect the wealth and assets of the owner. Similarly, currently existing security systems are rarely able to provide data directly to homeowners if an outsider wants to commit a crime. So, research was conducted with the title "Home Security Design with ESP32-CAM and Internet of Things (IoT) Based Alarm Notification Using Telegram Application". With this device plan, it is believed that individuals who leave the house will feel safer. This device can detect an infrared wave produced by humans within its range and is equipped with an alarm/buzzer that produces output in the form of notifications on Telegram and alarm sounds on the device. The PIR sensor and ESP32-CAM integrated with the Telegram mobile device form the basis of this security system. This research has successfully implemented a device aimed at reducing home burglary issues by detecting human motion, triggering alarms, and enabling remote monitoring through Telegram. Additionally, the adapter utilized in the system produces an average voltage value of 5.196 V with an average error rate of approximately 3.9%.